Pathogens inactivation in nutrient recovery from urine: A review - Xu, Kangning; Lu, Jun; Hu, Lanlan; Li, Jiyun; Cheng, Shikun; Zheng, Min; Wang, Chengwen (Frontiers in Environmental Science, 2022)
Urine source separation, a kind of new sewage management concept, has made great progress in technology development and application in the past 30 years. However, understanding of the potential microbial risks in reuse of urine-derived fertilizer products (UDFPs) in agriculture is still lacking. Outbreak of pandemic of Coronavirus Disease 2019 and more deadly disease caused by Monkeypox strongly sounds the alarm bell to the attention on pathogens in urine and their fate in UDFPs. Therefore, this study presented a comprehensive review on pathogens inactivation in nutrient recovery technologies. The review suggests that technologies using alkaline or heating treatment can effectively reduce pathogens in UDFPs. However, technologies with characteristics such as membrane rejection of nutrients or nutrient adsorption may even concentrate pathogens in their fertilizer products. Based on an overall assessment, connections of technologies and the pathogens inactivation in their UDFPs have been established. This would help to provide a perspective on development of urine treatment technology and management of microbial risks in reusing urine nutrients in agriculture.